COVID 19 in the Life of Hard of Hearing Students - Thakuri, Narayani (Janabhawana Research Journal, 2023)
The sudden and massive changes in the education system during COVID-19 and the introduction of online education have negatively affected hard-of-hearing students’ access to quality education. The pandemic situation worsened learning achievement and posed challenges to the students with hearing disabilities. With this consideration, a study was carried out to understand the students’ experience of taking online classes especially where they not only suffered from the fluctuation of the internet but also from their ringing ears caused by their tinnitus. The study applied the case study method with hard-of-hearing students to investigate the reasons influencing education during online classes during COVID-19. The collected data were thematized, analyzed and interpreted. The study findings demonstrated that the education system failed to consider the difficulties that students with hearing loss encountered in their learning leaving many teachers unaware of the issues that hard-of-hearing students face during online classes. The study concludes that online learning was not useful for the students with hard of hearing.